The relationship of redox signaling with the risk for atherosclerosis - Lei, Sujuan; Liu, Chen; Zheng, Tian-xiang; Fu, Wenguang; Huang, Mei-zhou (Frontiers in Pharmacology, 2024)
Oxidative balance plays a pivotal role in physiological homeostasis, and many diseases, particularly age-related conditions, are closely associated with oxidative imbalance. While the strategic role of oxidative regulation in various diseases is well-established, the specific involvement of oxidative stress in atherosclerosis remains elusive. Atherosclerosis is a chronic inflammatory disorder characterized by plaque formation within the arteries. Alterations in the oxidative status of vascular tissues are linked to the onset, progression, and outcome of atherosclerosis. This review examines the role of redox signaling in atherosclerosis, including its impact on risk factors such as dyslipidemia, hyperglycemia, inflammation, and unhealthy lifestyle, along with dysregulation, vascular homeostasis, immune system interaction, and therapeutic considerations. Understanding redox signal transduction and the regulation of redox signaling will offer valuable insights into the pathogenesis of atherosclerosis and guide the development of novel therapeutic strategies.